ANALISIS METODE PREFERENCE SELECTION INDEX DALAM MANAJERIAL EVALUASI KINERJA SUMBER DAYA MANUSIA - Laia, Angelus Aprianus; Aisyah, Siti; Togatorop, Aprianto; Marpaung, Dolly Martin (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
This research aims to solve the problem of performance assessment in a private company in the city of Medan. The quality of human resources (HR) is a key factor in achieving company goals, and performance appraisals often give rise to the effects of social jealousy among workers. To assist managerial parties in evaluating the performance of Human Resources, the Preference Selection Index (PSI) method is used to assist decision making. This research uses quantitative methods with employee data from the company's administration department as a sample by applying 4 assessment criteria such as performance, persistence, loyalty, discipline. Data collection involves interviews and direct visits to research locations. Data analysis was carried out by formulating a decision matrix, normalizing the data, calculating the normalized average value, preference variation value, determining the value in preferences, calculating the criteria weights, and calculating the overall preference value. The results showed that Individual 8 had the highest performance. This conclusion provides an overview of the extent to which employee performance meets the standards set by the company. This PSI method can be an effective tool in assisting management in making decisions regarding HR performance evaluation, by providing valuable information for understanding and increasing employee productivity.